Victorian produce monitoring program - Victoria. Department of Primary Industries (East Melbourne, Vic. : Dept. of Primary Industries.)
Includes results of Victorian government targeted chemical residue testing of fresh produce.
Description based on: 2000/01; title from PDF caption (viewed on Jan. 11, 2008)
Issues available in PDF format.
Also available in print.
Mode of access: World Wide Web
Selected for archiving
Keywords: Agricultural chemicals -- Environmental aspects -- Victoria -- Periodicals; Farm produce -- Victoria -- Periodicals; Pesticide residues in food -- Victoria -- Periodicals